Association between the dietary inflammatory index and the risk of hepatocellular carcinoma in a cirrhotic population - Rizk, Maud; Roux-Levy, Cécile; Bernard-Chabert, Brigitte; Bronowicki, Jean-Pierre; Richou, Carine; Habersetzer, François; Jouve, Jean-Louis; Hebert, James R.; Shivappa, Nitin; Boutron-Ruault, Marie-Christine; Diab Assaf, Mona; Hillon, Patrick; et al. (Clinical nutrition (Edinburgh, Scotland), 2025)
Hepatocellular carcinoma (HCC) is recognized as an inflammation-related cancer. However, the relation between inflammation deriving from the diet and HCC risk among cirrhotic patients has not yet been investigated. This study aimed to examine the association between the dietary inflammatory index (DII®) and HCC risk among cirrhotic patients. Clinical and dietary data were collected from the French case–control study CiRCE (Cirrhosis and Risk of hepatocellular Carcinoma in the East), which included 401 cirrhotic patients without HCC (controls) and 181 cirrhotic patients with HCC (cases) recruited between 2008 and 2012 in six French university hospitals. DII scores (36 food items and nutrients) were assessed using a validated self-administered diet history questionnaire. Odds ratios (OR) and 95 % confidence intervals (CI) were estimated with logistic regression models (adjusted for age, gender, time from cirrhosis diagnosis, etiology of cirrhosis, Child-Pugh score, and diabetes). The DII scores ranged between −4.77 and +7.59 with a mean value of 1.03 ± 2.87 among cases and 0.83 ± 2.87 among controls, indicating that both groups were following a pro-inflammatory diet. After multi-variable adjustment, there was a positive association between HCC risk and the DII score when considered as a continuous variable (ORcontinuous = 1.14 [1.02–1.27], p-value = 0.021) or categorized in tertiles (ORT3vsT1 = 2.33 [1.16–4.67], p-trend = 0.021). Similar results were found when alcohol was omitted from the DII calculation but considered as a co-variate: ORcontinuous = 1.15 [1.03–1.28], p-value = 0.013, and ORT3vsT1 = 2.35 [1.18–4.68], p-trend = 0.015. A positive correlation was observed between the DII scores and two inflammatory biomarkers (CRP, IL-6) among controls. The present study reported an association between a pro-inflammatory DII score and the risk of HCC in cirrhotic patients. Correlations between the scores and biological parameters support a potential role for inflammation in HCC among cirrhotic. Result should be confirmed in larger prospective studies, and could lead to nutritional prevention in cirrhotic patients. This study was registered in www.clinicaltrials.gov as NCT01798173.